2020
DOI: 10.1177/0363546520964486
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Anterior Cruciate Ligament Reconstruction and Relationship With Meniscal Tears: A Systematic Review and Meta-analysis

Abstract: Background: Anterior cruciate ligament (ACL) ruptures are common, but the ideal timing for ACL reconstruction after injury is unclear with regard to meniscal insult. Purpose: To determine whether there is a relationship between timing from ACL rupture to ACL reconstruction and development of meniscal tears within this period. Study Design: Systematic review and meta-analysis. Methods: A systematic literature search was undertaken independently by 2 reviewers using the Cochrane method for systematic reviews in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
(125 reference statements)
2
29
0
Order By: Relevance
“…Several studies reported that an increasing time from ACL injury to reconstruction was associated with a greater risk of secondary intra-articular lesions. 26,28,29 Additionally, the high prevalence of meniscal injuries during the revision procedure was highlighted by Yoon et al, 40 with a major association between concurrent meniscal tears and R-ACLR. Those authors reported that only 15 patients in a cohort of 86 patients (17.4%) had no tears, regardless of patient age.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that an increasing time from ACL injury to reconstruction was associated with a greater risk of secondary intra-articular lesions. 26,28,29 Additionally, the high prevalence of meniscal injuries during the revision procedure was highlighted by Yoon et al, 40 with a major association between concurrent meniscal tears and R-ACLR. Those authors reported that only 15 patients in a cohort of 86 patients (17.4%) had no tears, regardless of patient age.…”
Section: Discussionmentioning
confidence: 99%
“…26 Understanding the extent to which the decrease in surgical volume was due to decreased injury versus delayed surgery is important because studies have shown that ACLR delays are associated with worse outcomes. [10][11] It is customary to schedule ACLR within 3 months of injury due to the potential negative effects associated with delaying surgery, such as increased chondral lesions and increased risk of meniscal injuries and irreparable meniscal tears. [10][11] This became more difficult as many elective surgeries were delayed or cancelled due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11] It is customary to schedule ACLR within 3 months of injury due to the potential negative effects associated with delaying surgery, such as increased chondral lesions and increased risk of meniscal injuries and irreparable meniscal tears. [10][11] This became more difficult as many elective surgeries were delayed or cancelled due to the COVID-19 pandemic. [8][9] As providers counsel patients about preferred surgical timing for ACLR, both during the COVID-19 pandemic and beyond, they must consider the negative impact of delayed ACLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A delay to reconstruction of more than three months is associated with a higher incidence of medial meniscal tears. 41 In the past, early ACL reconstruction was often recommended, before episodes of instability occur in patients who continued sporting activities that involve sidestepping and pivoting. 38 However, the evidence that this occurs remains conflicting.…”
mentioning
confidence: 99%